Scientometrics of anesthetic drugs and their techniques of administration, 1984–2013 - Vlassakov KV; Kissin I (Dove Medical Press, 2014)
Kamen V Vlassakov, Igor Kissin Department of Anesthesiology, Perioperative and Pain Medicine, Brigham and Women’s Hospital, Harvard Medical School, Boston, MA, USA Abstract: The aim of this study was to assess progress in the field of anesthetic drugs over the past 30 years using scientometric indices: popularity indices (general and specific), representing the proportion of articles on a drug relative to all articles in the field of anesthetics (general index) or the subfield of a specific class of anesthetics (specific index); index of change, representing the degree of growth in publications on a topic from one period to the next; index of expectations, representing the ratio of the number of articles on a topic in the top 20 journals relative to the number of articles in all (>5,000) biomedical journals covered by PubMed; and index of ultimate success, representing a publication outcome when a new drug takes the place of a common drug previously used for the same purpose. Publications on 58 topics were assessed during six 5-year periods from 1984 to 2013. Our analysis showed that during 2009–2013, out of seven anesthetics with a high general popularity index (≥2.0), only two were introduced after 1980, ie, the inhaled anesthetic sevoflurane and the local anesthetic ropivacaine; however, only sevoflurane had a high index of expectations (12.1). Among anesthetic adjuncts, in 2009–2013, only one agent, sugammadex, had both an extremely high index of change (>100) and a high index of expectations (25.0), reflecting the novelty of its mechanism of action. The index of ultimate success was positive with three anesthetics, ie, lidocaine, isoflurane, and propofol, all of which were introduced much longer than 30 years ago. For the past 30 years, there were no new anesthetics that have produced changes in scientometric indices indicating real progress. Keywords: anesthetics, anesthetic adjuvants, mortality, safety margins, therapeutic indices